Fourier transform spectrometry - Davis, Sumner P. (Academic Press, 2001)
Fourier Transform Spectrometry is of immediate use to those who use Fourier transform spectrometers in their research, or are considering their use. The authors' presentations enable readers to obtain a clear understanding of FTS, which is crucial to their studies and research. Due to the increasing complexity and commercialization of instrumentation, achieving optimum performance in research applications and automated usage can be challenging. For example, a thorough understanding of the instrument can dramatically affect the outcome of the experiment and the generation of reliable data in applications where conditions are not ideal and resulting signals are weak. This book provides a comprehensive discussion of FTS from the ground up, covering basic concepts, instrumentation, data-processing algorithms, and techniques for computerized spectral analysis.